The Effects of Customer Personality Traits on the Display of Positive Emotions - Tan, Hwee Hoon; Foo, Maw‐Der; Kwek, Min Hui (Academy of Management Journal, 2004)
We extended past research on the display of positive emotions within customer service settings by focusing on customer traits. Adopting an emotional contagion perspective, we found that customer traits relate to the display of positive emotions by the service provider. This display of positive emotions was also found to relate to customer satisfaction. Implications for emotion management and service personnel training are discussed. The present study presents evidence that cus-tomers shape their own service experiences through their traits and through the display of pos-itive emotions by service providers. The field of emotion management has concentrated on service providers ’ display of positive emotions to custom-ers (e.g., Pugh, 2001; Rafaeli, 1989). Rafaeli and her colleagues proposed and tested several situational demands that affected the display of positive emo-